Evaluating the Physical and Rheological Properties of Rejuvenated Styrene-Butadiene-Styrene-Modified Asphalt Binders - Xiaobing Chen; Juntian Wang; Xiaorui Zhang; Han Liu; Jinhu Tong; Ronglong Zhao (Advances in Materials Science and Engineering)
To evaluate the physical and rheological properties of rejuvenated styrene-butadiene-styrene-modified asphalt (SBSMA) binders designed for rapid in-place pavement recycling, an aged SBSMA binder was rejuvenated with three rejuvenators (i.e., Types I, II, and III) in different dosages. The physical properties of rejuvenated SBSMA were obtained to determine the optimal type and dosage of rejuvenators for the first and second rejuvenation. Performance grade (PG) tests, multiple stress creep recovery (MSCR) tests, and linear amplitude sweep (LAS) tests were conducted to measure the rheological properties using the dynamic shear rheometer (DSR) and bending beam rheometer (BBR). The results exhibited that the rejuvenators could soften the multiple aged binder and enhance its high- and low-temperature performance. The rejuvenation effect of rejuvenator Type I with the optimal dosage of 6∼8% was the most appropriate for the first rejuvenation. The optimal dosage of the second rejuvenation was 10∼12%. The addition of rejuvenators decreased the rutting factor G∗/sin δ, creep stiffness (S), delta Tc (ΔTc) parameter, recovery response (R), and yield stress of rejuvenated SBSMA. On the other hand, an increase in the rate of relaxation (m-value), nonrecoverable creep compliance (Jnr), and yield strain of rejuvenated SBSMA was recorded. Overall, the study findings indicated an improvement in the elastic properties of rejuvenated SBSMA, which contributes to improving the rutting, thermal, and fatigue cracking resistance of asphalt binder and ultimately the response of asphalt pavements.